2015
DOI: 10.1007/s10620-015-3629-5
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Inflammatory Bowel Disease: A Marker of Less Severe Disease

Abstract: Obesity is highly prevalent in our IBD patients, paralleling the obesity rates in the US population. Clinical outcomes were significantly different in obese versus non-obese patients with IBD. Despite the plausible mechanisms whereby obesity might exacerbate IBD, we have found that obesity (as defined by BMI) is a marker of a less severe disease course in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(161 citation statements)
references
References 28 publications
10
133
4
2
Order By: Relevance
“…Whereas the prevalence of malnutrition and underweight has decreased over the past years [30], patients with IBD are more often overweight or obese now, probably as a result of improved therapeutic options and prolonged remission status [31,32]. Our study data confirmed this trend.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Whereas the prevalence of malnutrition and underweight has decreased over the past years [30], patients with IBD are more often overweight or obese now, probably as a result of improved therapeutic options and prolonged remission status [31,32]. Our study data confirmed this trend.…”
Section: Discussionsupporting
confidence: 81%
“…According to the BMI-classification of the World Health Organization (WHO), a BMI less than 18.5 kg/m² was considered as underweight, between 18.5 kg/m² to 25.0 kg/m² as normal weight, between 25.0 kg/ m² to 30.0 kg/m² as overweight (pre-obese) and over 30.0 kg/m² as obese [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Nutritional Statusmentioning
confidence: 99%
“…Thus, between 15 and 40% of IBD patients are now reported as overweight or obese [3,4]. Nutrition screening of all inpatients is mandatory and routinely carried out in the health services of certain countries.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that despite aforementioned causes leading to malnutrition in IBD, one-third of the patients are obese, the proportion is similar in CD and UC patients [45,46]. Obese IBD patients do not have worst long-term clinical outcome than normal weight patients [47].…”
Section: Nutritional Status Of Ibd Patientsmentioning
confidence: 99%